NUTRIEN PEMBATAS DI EAST RIVER, KOREA - Aditya Rahman KN (Universitas Lambung Mangkurat, 2010)
This study presents information on physico-chemical and nutrients that limit the water of East River, Korea. Collected water samples from 16 main streams and 7 branches in MayNovember 2008 were measured for their heavy metal and nutrients concentration. Nutrient enrichment bioassay tests with the use of Nitzschia pungens was also conducted. This threeseason study indicated that the phosphorus was the limiting factor for algal growth.